Determination of the PAH metabolites in human urine by high-performance liquid chromatography - G V Zykova; S Y Semenov; V N Smirnov (RUDN Journal of Ecology and Life Safety, 2014)
Measurement technique of the primary metabolite indicator - 1-hydroxypyrene in human urine is developed for the purposes of the human exposure to polycyclic aromatic hydrocarbons biomonitoring. The technique is based on the HPLC with a fluorescence detector use employing an internal standard method.